Large synaptic genes are more frequently affected by somatic mutations and show reduced expression in Alzheimer's disease: Implications for disease etiology: Genetics/genetic factors of Alzheimer's disease. (7th December 2020) - van der Linden, Robert J.; Soheili‐Nezhad, Sourena; Sprooten, Emma; Poelmans, Geert
Abstract: Background: Aging is associated with the accumulation of somatic mutations in post‐mitotic neurons. While this idea is not new, recent advances in single‐cell sequencing techniques have now made it possible to not only unequivocally prove that these mutations occur but also to estimate their occurrence rates. Here, we aimed to investigate whether somatic mutations are associated with Alzheimer's disease (AD) and gain insight into the potential pathophysiological consequences of such mutations in the brain. Method: Starting from the average annual somatic variation rate of healthy neurons, we modeled the likelihood of a gene being affected by somatic mutations over time, based on the transcribed length of that gene. Subsequently, we investigated the gene length distribution of genes that are affected by somatic mutations in AD brains and we analyzed differential mRNA expression data from eight AD brain areas, including pathway analysis. Result: Our model predicted that CNTNAP2, the largest gene in the human genome, has a 50% chance of having acquired at least one somatic mutation by the age of 65, which is in sharp contrast with average‐sized genes, in which there is only 1% chance of somatic mutations at 65. We also found that genes affected by somatic mutations are (much) longer than average and that larger genes are more likely to be reduced in their expression levels in AD‐vulnerable brain regions. Lastly, we found that these larger genes are predominantly expressed in neurons and are involved in synaptogenesis and synaptic adhesion, pathways that are predicted to be inhibited in AD based on the transcriptomic data. Conclusion: Our findings implicate somatic mutations in large genes as potential contributors to AD pathology through their effect on synaptic function.